Fabrication of Colloidal Cesium Metal Halide (CsMX: M = Fe, Co, and Ni) Nanoparticles and Assessment of Their Thermodynamic Stability by DFT Calculations - Kwon, Hyo Geun; Ryu, Jehyeon; Park, Jong Goo; Park, Sang Woo; Kwon, O. Pil; Hong, Ki Ha; Kim, Sang Wook (Inorganic Chemistry, 2022)
We synthesized colloidal cesium metal halide CsMX (M = Fe, Co, Ni; X = Cl, Br) nanoparticles (NPs) and assessed their crystal stability by density functional theory (DFT) calculations. We successfully synthesized Cs3FeCl5, Cs3FeBr5, Cs3CoCl5, Cs3CoBr5, CsNiCl3, and CsNiBr3NPs. CsMX NPs with Fe and Co exhibited Cs3M1X5and Cs2M1X4structures depending on the reaction conditions; however, CsNiX NPs exhibited only the CsNiX3structure. The differences in structural stability by central metal ions were explained using spin-polarized DFT calculations. The analysis revealed tetragonal Cs3M1X5and orthorhombic Cs2M1X4structures to have similar thermodynamic stabilities in the case of Fe and Co, whereas the hexagonal CsMX3structure in the case of Ni was the most stable. Moreover, the calculation results were the same as the experimental results. In particular, cobalt-related Cs3CoBr5NPs easily developed into Cs2CoCl4nanorods with an increase in temperature.
Keywords: Co and Ni; Co Nanoparticles; Crystal stability; Density-functional theory calculations; Fe and Co; Fe nanoparticles; Ni Nanoparticles; Reaction conditions; Structural stabilities; Synthesised